International Students' Challenges and Opportunities - Bay, Shing Yee; Agarwal, Saudamini; Cable, Charissa B.; Goodman, Jeffrey A. (My University, 2018)
In the present study, we attempted to gain insights into the particular challenges and opportunities for success for international students at UW-Eau Claire. We conducted focus groups in an effort to obtain rich information and to uncover themes common to international students on our campus.
Color poster with text and images.
Keywords: Posters; International students; Study abroad; Race relations on campus